Peak V’O2 is an independent predictor of survival in patients with cardiac amyloidosis - Hein, Selina; Siepen, Fabian aus dem; Bauer, Ralf; Katus, Hugo; Kristen, Arnt (Amyloid, 2018)
Introduction: Cardiopulmonary exercise testing (CPET) has repeatedly been reported to reliably predict adverse outcomes in different forms of heart failure. However, it has not been elucidated in detail in cardiac amyloidosis (CA). Therefore, we evaluated the predictive value of CPET parameters in patients with CA regarding disease severity and prediction of mortality.Methods: Twenty-seven consecutive patients with CA were assessed noninvasively, including electrocardiography, echocardiography, CPET, and laboratory tests. Clinical data were correlated with CPET findings. Univariate and multivariate analyses were performed to evaluate predictors of mortality.Results: Within median follow-up period of 38 (IQR 43) months 19 (70%) deaths occurred. Patient initially presented with signs and symptoms of congestive heart failure NYHA 3 (IQR 1), reduced exercise capacity (peak V’O2 15.2 mL/kg body weight) and inefficient ventilation in CPET (V’E/V’CO2 slope (30 (IQR 3)), markedly elevated cardiac biomarkers (NT-proBNP 1791 (IQR 3249) ng/mL) and echocardiographic signs of morphological (septum thickness 18 (IQR 6) mm) and functional cardiac involvement (TAPSE 19 (IQR 8) mm). Patients with peak V’O2 below median value presented with significantly longer QTc interval when compared to patients with peak V’O2 above the median. Further these patients tend to have more pronounced impairment of longitudinal function as indicated by lower MAPSE, TAPSE, and elevation of cardiac biomarkers. Multivariate analysis revealed peak V'O2 slope as the only independent predictor of survival.Conclusions: We identified reduced peak V'O2 as an independent predictor of mortality in patients with cardiac involvement in different forms of systemic amyloidosis.
Published online: 07 Sep 2018
Gesehen am 26.08.2019